PENGARUH STRATEGI PEMASARAN ONLINE TERHADAP MINAT BELI KONSUMEN DI KOTA MAKASSAR (STUDI KASUS TOKO RAMADHAN STATIONERY) - Rasyid, Muh Nur; Nasrullah, Nasrullah; Sumarni, Sumarni (Universitas Muhammadiyah Makassar, 2021)
This research was conducted with the aim to determine whether or not the influence of online marketing strategies on consumer buying interest in paperbag, book and pen at Ramadhan Stationery stores. The research used in this study used a quantitative, where this study used a questionnaire as a data collection tool. The design of this survey method is descriptive quantitative. The sampling method uses the slovin formula, where the entire population is sampled. Data collection techniques using questionnaires, field observations and interviews.This research is a descriptive quantitative research design because it is a concept development and data collection to examine the effect of online marketing strategies on consumer buying interest, a case study of Ramadhan Stationery Stores in Makassar City. From the results of the regression analysis using the SPSS 26 program, the coefficient value of the influence of marketing strategies on purchase intention is 0.818 with a value of p = 0.000 <0.0, this is supported by the results of the t test, namely the t value of 12.336 with a significance of 0.000 and t table of 1, 98447 with a specified significance level of 0.05 or 5%. This shows that the marketing strategy has a significant positive effect on consumer buying interest in the City of Makaassar (Case Study of Ramadhan Stationery Stores), this means that the better the marketing strategy carried out at Ramadhan Stationery Stores, the more consumers' buying interest in Ramadhan Stationery Stores will increase.Keywords: Online Marketing Strategy, Consumer Purchase Interest